Progression of visual cognition and neuropsychiatric symptoms in Huntington’s disease: a 1-year follow-up study across preclinical and clinical phases - Del Pino, Rocio; Acera, Maria Ángeles; Murueta-Goyena, Ane; Tijero, Beatriz; Ruiz-Lopez, Marta; Somme, Johanne; Pérez-Fernández, Silvia; Ruiz, Javier; Gabilondo, Andrea; Sánchez-Pernaute, Rosario; Gabilondo, Iñigo; Fernández-Valle, Tamara; et al. (Frontiers in Psychology, 2025)
IntroductionHuntington’s disease (HD) is a progressive and complex neurodegenerative disorder marked by motor, psychiatric, and cognitive impairments. This study evaluates the progression of visual cognition across the HD spectrum—including pre-manifest with reduced penetrance (RP) alleles—as a potential early marker of disease progression. Secondary objectives assess changes in motor function, general cognition, and neuropsychiatric symptoms, and identify predictors of clinical trajectories. Exploratory analyses focused on the characterization of pre-manifest and RP individuals compared to HD-manifest carriers.MethodsWe assessed 181 participants at baseline and 1-year follow-up: 40 pre-manifest HD, 30 early-manifest HD, 27 manifest HD, 6 RP, and 78 healthy controls (HC). Visual cognition, motor and general cognitive function, neuropsychiatric symptoms, premorbid intelligence, and quality of life was evaluated. Linear mixed models were applied, including models excluding HC and integrating years to estimated motor onset.ResultsVisual cognition, especially visual memory and attention, emerged as a sensitive domain for early decline across the HD spectrum. Pre-manifest individuals showed significant worsening in visual memory compared to HC, while RP carriers exhibited additional changes in visual attention and processing speed despite preserved motor status. Excluding HC and using pre-manifest group as reference, significant longitudinal decline was confirmed in visual domains (memory, attention, processing speed, visuospatial abilities), and verbal fluency, with years to estimated onset and premorbid intelligence emerging as consistent predictors. Motor performance and general cognition declined mainly in early- and manifest carriers. Neuropsychiatric symptoms worsened across the spectrum, with manifest patients most affected. RP carriers presented the highest levels of suicidal ideation, significantly higher than pre-manifest individuals. Protective factors included higher premorbid intelligence, better daily functioning, quality of life, and lower baseline apathy and suicidal ideation.ConclusionVisual cognitive decline— particularly memory and attention—represents an early and sensitive marker of disease progression in HD, even in asymptomatic carriers. Emotional vulnerability, including elevated suicidal ideation in RP individuals, further highlights the need for close monitoring of this under-characterized subgroup. These findings support the integration of visual cognition and neuropsychiatric assessments into early detection frameworks, with direct implications for personalized interventions and preventive strategies in prodromal stages.